Estudo das propriedades estruturais e de transporte eletrônico em nanoestruturas de óxidos semicondutores e metálicos - Berengue, Olivia Maria (2010)
The structural and transport features of oxide nanostructures synthesized by a vapour phase aproach: the VLS and VS methods were investigated in this work. ITO and In2O3 nanowires were characterized by using XRD, HRTEM and FEG-SEM techniques. Both nanostructures were found to be body-centered cubic (bixbyite, point group Ia3) single crystals with a well defined growth direction. Raman spectroscopy was used in order to study the nanowires composition, crystalline character and the role of tin atoms in the In2O3 lattice (ITO) was studied as well. The influence of the structural disorder induced by doping was pointed as the main cause of the break of the selection rules in ITO and it was promptly recognized in the Raman spectrum. The metallic character observed in In2O3 micrometric wires was assigned to the electron-phonon scattering in agreement with the Bloch-Grüneisen theory. ITO samples with different sizes were analysed in the framework of the Bloch-Grüneisen theory and at high temperatures (T > 77 K) they were found to present a typical metallic character. It was observed at low temperatures (T < 77 K) and in small samples a negative temperature coefficient of resistance which is an evidence that quantum interference processes are present. A weak localized character was found in these samples as detected in magnetoresistance measurements. The electron s phase break was associated to the electronelectron scattering (T < 77 K) and the electron-phonon scattering (T > 77 K). The transport measurements in one-nanowire based FET provided data on the electron s mobility and density. Tin oxide nanobelts were also studied and their structural and electrical characterizations were obtained. In this case the association of several structural measurements provided that the samples are rutile-like single crystals (point group P42/mnm) grown by the VS mechanism. The transport measurements provided data on the nanobelts gap energy (3.8 eV) and on the transport mechanisms acting in different temperature ranges. An activated-like process and the variable range hopping were found to be present in different temperature range and additionally the localization length was determined. The influence of additional levels inside the gap caused by oxygen vacancies was studied by performing light and atmosphere-dependent experiments and as a result a photo-activated character was detected. Thermally stimulated current measurements provided evidence that only one level associated to the oxygen vacancies at 1.8 eV seems to contribute to the transport in SnO2 nanobelts. Triclinic single crystalline nanobelts were identified as the Sn3O4 phase and were analyzed by transport measurements. The samples were wide band gap semiconductors and the role of oxygen vacancies was identified by using PL and PC measurements. The semiconductor behavior was confirmed by the electron transport data, which pointed to the variable range hopping process as the main conduction mechanism (55 K < T < 398 K) and data on localization length and on the hopping distance were obtained. The presence of additional levels due to oxygen vacancies and tin interstitials was recognized in the samples by performing photo-activated and thermally stimulated current measurements.